Why Leadership Matters - Hunter, Susan (Maine Policy Review, 2018)
This essay is from a talk University of Maine President Dr. Susan J. Hunter gave on May 30, 2018, at Bangor Public Library as part of Dirigo Speaks. President Hunter feels her time at UMaine has allowed her many opportunities to reflect on leadership and why it matters, and recognizes that many people have shaped her perspectives on leadership.